Optical coherence tomography in late solar retinopathy - Janković Aleksandar; Vukosavljević Miroslav; Avramović Siniša; Draganić Biljana (Vojnosanitetski Pregled)
Introduction. Solar retinopathy refers to retinal injury induced by direct or indirect solar viewing. Case report. We presented a patient who had observed partial solar eclipse 51 year before. He had bilaterally decreased vision and scar of the macular region at the time of presentation. The basic diagnostic tool applied in the presented patient, optical coherence tomography, showed hyporeflexivity of the outer retina in the segment of retinal pigment epithelialphotoreceptors complex with atrophy and thinning of the foveolar region. Conclusion. Optical coherence tomography is a powerful, non-invasive diagnostic tool which can ease the diagnosis and estimate the level and nature of the macular region damage.